2021
DOI: 10.1186/s12861-021-00238-4
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of hspg2 is associated with abnormal mandibular joint formation and neural crest cell dysfunction in zebrafish

Abstract: Background Heparan sulfate proteoglycan 2 (HSPG2) encodes for perlecan, a large proteoglycan that plays an important role in cartilage formation, cell adhesion, and basement membrane stability. Mutations in HSPG2 have been associated with Schwartz-Jampel Syndrome (SJS) and Dyssegmental Dysplasia Silverman-Handmaker Type (DDSH), two disorders characterized by skeletal abnormalities. These data indicate a function for HSPG2 in cartilage development/maintenance. However, the mechanisms in which HS… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 57 publications
2
1
0
Order By: Relevance
“…We showed that Frk is expressed in the affected craniofacial tissues (Meckel's cartilage center or mandible bone) during the developmental period (Ling et al, 2017; Sisson et al, 2015). Furthermore, we demonstrated that morpholino‐knockdown of frk in embryonic zebrafish results in impaired development of Meckel's cartilage and associated tissues as well as abnormal mandibular joint formation, consistent with the affected individual's craniofacial developmental defects and other related disorders that have been modeled in zebrafish (Castellanos et al, 2021; Liu et al, 2021; Wang et al, 2020). These observed defects are consistent with improper regulation of sensory neurons in invertebrate systems and cranial neural crest cells (CNCC) in vertebrate systems, which may result in failure migrate to and differentiate into appropriate tissue in the head regions, including the pharyngeal arches, cartilage, and bone (Bhatt et al, 2013).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…We showed that Frk is expressed in the affected craniofacial tissues (Meckel's cartilage center or mandible bone) during the developmental period (Ling et al, 2017; Sisson et al, 2015). Furthermore, we demonstrated that morpholino‐knockdown of frk in embryonic zebrafish results in impaired development of Meckel's cartilage and associated tissues as well as abnormal mandibular joint formation, consistent with the affected individual's craniofacial developmental defects and other related disorders that have been modeled in zebrafish (Castellanos et al, 2021; Liu et al, 2021; Wang et al, 2020). These observed defects are consistent with improper regulation of sensory neurons in invertebrate systems and cranial neural crest cells (CNCC) in vertebrate systems, which may result in failure migrate to and differentiate into appropriate tissue in the head regions, including the pharyngeal arches, cartilage, and bone (Bhatt et al, 2013).…”
Section: Discussionsupporting
confidence: 75%
“…Furthermore, we demonstrated that morpholino-knockdown of frk in embryonic zebrafish results in impaired development of Meckel's cartilage and associated tissues as well as abnormal mandibular joint formation, consistent with the affected individual's craniofacial developmental defects and other related disorders that have been modeled in zebrafish (Castellanos et al, 2021;Liu et al, 2021;Wang et al, 2020) As SRC kinase family members, human FRK and FYN (OMIM *137025) share high identity/similarity in protein sequence (46%/59%) and have been linked to tumorigenesis due to their overexpression or somatic mutations (OMIM *606573). Knockout of the mouse ortholog gene Frk was found to cause significant decreases in the circulating levels of T3 and euthyroid sick syndrome (ESS) (Chandrasekharan et al, 2002).…”
Section: Discussionsupporting
confidence: 66%
“…HSPG2 encodes for perlecan, a large proteoglycan that plays an important role in cartilage formation, cell adhesion, and basement membrane stability. The diseases related to HSPG2 mutations mainly include dyssegmental dysplasia Silverman-Handmaker type (DDHS) and Schwartz Jampel syndrome type 1, both of which are autosomal recessive diseases [ 24 ]. The clinical features of DDHS include facial dysmorphisms, GU abnormalities, severe short stature, decreased joint mobility, cleft palate and club feet [ 25 ].…”
Section: Discussionmentioning
confidence: 99%